Medicinal Plant Informatics- An Insight - P.T.V., Lakshmi (Pharmacognosy Communications)
The renaissance on traditional usage of medicinal plants as drugs for various human ailments has increased interest in the search for information on plant medicinal systems. A demand by the pharma-industry on the sources and availability of the lead compounds from plants has inculcated the research across the globe. This has proportionately provided us with a wealth of data which needs a classical and a dedicated approach for easy identification. Based on this view, many different databases have emerged that contain enormous amounts of information on the phyto-constituents, biological properties of various plant species and the possible strategies that could be adopted to extract and explore these in an effective manner. Since this information is stored as mixture of online and commercial resources, identifying them become a difficult task. Hence the approach outlined in this review is useful to comprehend the surplus data available on these web resources so that any reader could be aware on the specific database as well as the information system that it carries for a better understanding and exploration in the future.
Keywords: databases; exploration; medicinal plants; pharma-industry; phyto-constituents